The Primates of Susa: Depictions of Monkeys in Stone Statuettes from Elam - Urbani, Bernardo (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2021)
In the Near East and the Eastern Mediterranean region there is a lack of proper taxonomic identification when referring to material culture depicting primates. A group of five primatomorphic statuettes from Susa of the Proto-Elamite and Elamite periods deserves a closer examination. Two monkey species were identified: olive baboon (Papio anubis) and rhesus macaque (Macaca mulatta). Olive baboons naturally range in western and central-eastern Africa, while rhesus macaques are distributed in western central Asia and the Indus River Valley. Considering this evidence, Susa might have served as a Near Eastern trading post for the circulation of primates or primate imageries since the 4th and 3rd millennia BCE. These statuettes are among the earliest depictions of primates made by a Near Eastern civilization and a civilization in the world.